The Effect Of Gumboro Disease On The Incidance Of Airsacculitis Caused By Esherichia Coli - Shalash, Ali A.H.; AL-Saeg, M. H. (The Iraqi Journal of Veterinary Medicine, 2004)
This study was conducted to investigate the effect of Gumboro disease virus (IBDV) on the incidance of airsacculitis induced by E. coli after infection with (IBDV). The study included 240-day-old broiler chicks, which were divided equally into four groups and treated as follow: Group1 (G1): given 0.1ml of (IBDV) that contain 105.1 EID50 / ml in the crop at day 21 of age. Group2 (G2): treated as G1 than given 0.1 ml of E. coli sero type (0.88:H-) that contain 12x108 CFU/ml in the treachea at day 28 of age. Group3 (G3): given E. coli only on day 28 and in the same method as G2. Group4 (G4): given 0.1ml saline in the trachea at day 28 of age (untreated control). The rate of mortality after infection with (IBDV) in the both G1 and G2 was (11.6%). After infection with E. coli the mortality rate in G2 was (27.7%) while G3 showed mortality rate (13.3%). There was a significant difference (P<0.05) between G2 and G3 in mortality rate concluded that experimental infection of broilers at day 21 off age with (IBDV) increased the susceptibility of the chickens to incidance of airsacculitis induced by E. coli.